Metaphorical conceptualisation of the domain of healthcare and medicine in the English language - MIlošević, Ivan (Education and Research in Health Sciences, 2025)
Introduction: This paper deals with the metaphorical conceptualisation of healthcare/medicine in the English language employing the theoretical framework of cognitive linguistics. In other words, based on the language material obtained from journalistic articles/texts in the field of health, healthcare and medicine, the paper investigates a variety of source domains whose elements and relations conceptualise the target domain of healthcare/medicine.Objective: The primary objective of this paper is the determination of the potential metaphorical conceptualisation of the English language for healthcare and medicine, that is, the identification of the source domains which semantically motivate the target domain of healthcare/medicine and the metaphors which construe the conceptual framework of the linguistic expressions investigated in this research.Method: A qualitative semantic analysis of the corpus-oriented linguistic units in the light of methodological apparatus of cognitive linguistics.Results: The semantic investigation of the observed metaphorical expressions relating to the concept of healthcare/medicine provides a list of 15 different source domains which motivate their semantic dimensions via numerous conceptual metaphors forming systematic mappings between the source domains and the concepts in the target domain of healthcare/medicine.Conclusion: The paper concludes that the language of healthcare and medicine used in the journalistic discourse reflects a high degree of metaphoricity, which stems from the profound cognitive entrenchment of the linguistic units belonging to the target domain of healthcare/medicine under exploration in this paper.
Keywords: conceptualisation; source/target domain; metaphorical expressions; conceptual metaphors; HEALTHCARE/MEDICINE; journalistic discourse